RNA-Seq Analysis on the Microbiota Associated with the White Shrimp (Litopenaeus vannamei) in Different Stages of Development - Raúl Enrique Valle-Gough; Blancka Yesenia Samaniego-Gámez; Javier Eduardo Apodaca-Hernández; Francisco Xavier Chiappa-Carrara; Mauricio Rodríguez-Dorantes; María Leticia Arena-Ortiz (Applied Sciences, 2022)
White leg shrimp (Litopenaeus vannamei) is a widely cultured species along the Pacific coast and is one of the most important crustaceans in world aquaculture. The microbiome composition of L. vannamei has been previously studied in different developmental stages, but there is limited information regarding the functional role of the microbiome during the development of L. vannamei. In this study the metatranscriptome in different developmental stages of L. vannamei (larvae, juvenile and adult) were generated using next generation sequencing techniques. The bacterial phyla found throughout all the stages of development belonged to the Proteobacteria, Firmicutes and Actinobacteria, these bacterial phyla are present in the digestive tract and are capable of producing several hydrolytic enzymes, which agrees with high representation of the primary metabolism and energy production, in both host and the microbiome. In this sense, functional changes were observed as the development progressed, in both host and the microbiome, in stages of larvae the most represented metabolic functions were associated with biomass production; while in juvenile and adult stages a higher proportion of metabolic functions associated to biotic and abiotic stress in L. vannamei and the microbiome were shown. This study provides evidence of the interaction of the microbiome with L. vannamei, and how the stage of development and the culture conditions of this species influences the gene expression and the microbiome composition, which suggests a complex metabolic network present throughout the life cycle of L. vannamei.